PENINGKATAN KEMAMPUAN MENULIS DONGENG SISWA KELAS VII SMP NEGERI 1 BENGKULU SELATAN DENGAN TEKNIK MODIFIKASI CERITA - Resmasita, Resmasita (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2015)
The purpose of the research is to know  the increase of the ability to write a fairy tale for the seventh grade student of SMPN 1 South  Bengkulu by using Story Modification Technique. This research constitutes Classroom Action Research. This research is held some phases. Namely :  a). Planning Phase b). Observation Phase 3). Exercution Phase, and 4. Reflection Phase and so on until improvement or increase can be reached. The Data Collecting Instruments is by using ; a). Observation (Teacher’s observation sheet and Student’s observation sheet) b). Assessment Sheet of  the ability to rewrite story. Technique analysis data; a). Determining students` average score b). Determining classical completeness and c). Determining conclusion. Based on the analysis data, the modification technique story can raise the ability to write a fairy tale. This research is held in two cycles. At the first cycle, the result of student’s learn can be presentation 23% classical completeness and 68 average score. The second cycle is for remedy  by guiding, giving motivation to the students and giving an example of story which had been modified by a teacher. The 81 average score, that showed 82% of classical mastery completeness. From both of cycles, we can see that there are increases taken place in form of the students` result in learning. So, , the research is done. From the classroom action research, it can be seen that the ability to write a fairy tale of the seventh grade students of SMPN 1 South Bengkulu is raised by using the Story Modification Technique.Keywords: The increase of ability to write a fairy tale, story modification.